Asuhan Keperawatan Pada Ny. D Dengan Gangguan Sistem Reproduksi : Kista Ovarium Di Ruang Nusa Indah RSUD Dr. Soeselo Kabupaten Tegal - Umi Mahmudah; Tati Karyawati; Siti Fatimah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Ovarian cyst is one of the most common reproductive system disorders among women of reproductive age, often asymptomatic and discovered only during advanced stages. This study aimed to describe the nursing care process for a patient diagnosed with ovarian cyst using a comprehensive nursing approach. A descriptive case study was conducted on a patient named Mrs. D, hospitalized at Nusa Indah Ward of RSUD dr. Soeselo, Tegal. Data were collected through interviews, observation, physical examination, and documentation. The identified nursing diagnoses included acute pain, anxiety, knowledge deficit, risk of infection, and nutritional risk. Interventions were implemented according to the Indonesian Nursing Intervention Standards (SIKI), including non-pharmacological pain management and patient education. The evaluation showed improvement in pain levels, anxiety, and patient understanding of the disease. This study confirms the importance of comprehensive and holistic nursing care in managing ovarian cyst patients, especially through effective communication and collaboration with multidisciplinary teams.